Giant mediastinal parathyroid adenoma presenting as bilateral brown tumour of mandible: a rare presentation of primary hyperparathyroidism - Talukder, Shibojit (BMJ Case Rep, 2017)
Hyperparathyroidism (HPT) is becoming increasingly common endocrinopathy in clinical practice. Nowadays, it is mostly diagnosed in subclinical or early clinical stage. Bony involvement in HPT has seen significant fall in incidence. Brown tumour of bone is exceptionally rare as a first manifestation of primary HPT (PHPT). Its radiological and histopathological features may be mistaken for other bony pathologies. If possibility of underlying HPT is overlooked the disease is bound to recur after surgery adding to morbidity of the patient. Here we present a case of bilateral brown tumour of mandible which was mistakenly treated as giant cell granuloma by surgical curettage. That the patient was harbouring an ectopic parathyroid adenoma with hypercalcemia causing non-specific symptoms was missed by the referring physician. This led to recurrence of the lesion. On subsequent evaluation, a giant mediastinal parathyroid adenoma causing PHPT was detected at our centre and was removed via mini sternotomy approach.